THE CONCEPTS «LIFE CREATIVITY» AND «LIFE CREATIVE COMPETENCE» IN THE PARADIGM OF PROFESSIONAL TRAINING OF A SPECIAL EDUCATION TEACHER - Lyudmila M. Nikolenko (Alfred Nobel University Publisher, 2022)
The article deals with the problem of the competence approach in education. The article is based on careful analysis of the scientific literature and highlights the concept of "life-creating competence". The necessity and expediency of such competence forming in the future special education teacher result from the practice of living in an open information society, where the individual is required to show a new level of abilities that could ensure his/her effective functioning in any dynamic changes and circumstances, successful and comprehensive life both in personal and professional spheres. The article analyzes the subject matter of the life creation concept in philosophical, psychological and pedagogical aspects. A review of the scientific literature demonstrated that in philosophical and sociological discourse life-creation is mainly considered in the perspective of one's own life building and culture of life creation, and it made it possible to highlight the following points: life-creation is a process based on two constitutive components: life and creativity; these components are purely individual; life creation depends on both personal characteristics and social factors; the individual must be in some way ready to carry out life creativity; thus, consequently, life-giving competence can be an indicator of readiness for life-creation. It was found that psychology studied the problem of life creation most thoroughly; psychologists present life creation as a manifestation of the subject's personality, an active attitude to life, the result of self-development, a special type of life, etc. The author found that the life of an individual is one of the key phenomena in the philosophy of education, where it is considered in terms of the activity approach: it is a special kind of life, creative activity of the individual, life-creation, the art of living. One of the determining factors of life creation is education. In terms of pedagogy, the study of life creation of an individual at the beginning of the 21st century has grown into a separate area - the pedagogy of life, which formed the basis of the concept of the New Ukrainian School. It was found that the phenomenon of "life-creating competence" in pedagogy is not considered as a separate achievement of an individual, but there is "life-creating competences", represented as a component of life competence of that individual. Based on the analytical review, the author summarizes that life competence provides the solution of vital tasks, productive life, the ability to perform certain life roles; life-creating competence, according to the author, brings an individual to a higher level of life, at which a person realizes self-design, selfconstruction, self-education and other self-practices; it is an active, creative and responsible subject of his/ her own life and social development, as he/she is able not only to adapt to dynamic circumstances, but also to change the environment for the benefit of him/herself and others, which is crucial for special education teachers in the light of modern educational paradigm.